Adaptive joint tracking approach of system parameters and the time delay - Pupeikis, Rimantas (Lietuvos matematikos rinkinys, 2017)
The problem of adaptive joint parameters and the time delay tracking is tackledby processing of input-output observations, when nonstacionary dynamical system has anunknown time delay. The recursive approach based on the method of corrective operatorsis developed for their tracking. Applicability of algorithms is supported by simulation testson a computer.
Keywords: adaptive system; parameters; tracking; estimation; time delay